An empirical test of groundwater pumping effects on river flow and temperature: Chemainus River case study. Issue 1 (2nd January 2023) - Wright, Nicole; Hatfield, Todd
Abstract: Groundwater abstraction from pumping wells can reduce the flows and water levels of hydraulically connected surface waters, which can affect aquatic communities and water rights of other users. Four pump tests were implemented in the 2016 summer low-flow period to measure groundwater pumping effects to Chemainus River surface water flow and temperature. The effect of pumping on surface flow was estimated using four metrics based on differences between measured and predicted flow at a hydrometric gauge located 340 m from the groundwater wells. Differences were estimated as residuals from a regression model relating flow at this gauge to flow at a gauge 1.3 km upstream of the wells. The effect of pumping on surface water temperature was assessed using daily maximum and daily average water temperature at gauges located 340 m and 1.4 km downstream of the wells. An effect of pumping on river flow was measurable when the pumps were turned on and shut off. The consistency of measured effects across all tests and the absence of discernable trends within and across tests indicate that the average effect of pumping across a broader period is equivalent to the average of all before and after comparisons, which was estimated as 9.9 L/s ± 12.1 L/s, or 5.5% of river discharge at the time of the tests. Groundwater pumping did not result in a detectable shift in water temperature. The results indicate that changes in water temperature in relation to the pump tests were smaller in magnitude or spatial scale than the detection limits of the implemented experimental design. This case study provides an example of quantification of pumping effects on stream flow and temperature, as required by the Water Sustainability Act for licensing of groundwater abstraction. We suggest this approach could be used elsewhere to quantify effects of groundwater abstraction.